Blood, death, and data: Engaging medical science and technology studies - Hoeyer, Klaus (STS Encounters, 2014)
From the introduction: Over the course of relatively few years, science and technology studies (STS) has become recognized as an internationally significant discipline and is today well known also in Danish academia. The present paper serves to inaugurate a chair in medical science and technology studies. What is this? I think of the subfield of medical science and technology studies (mSTS) as the study of how social, political, and cultural practices shape medical research, technological innovation, and clinical routines and how these, in turn, affect society, politics, and culture. In other words, it is about exploring the co-production of science and society in a way that, in effect, dissolves clear distinctions between the social and the technological, between semantics and materiality, between culture and nature (Jasanoff, 1990; Jasanoff, 1995; Jasanoff, 2005). It is the study of medical research and clinical practice from a theoretically informed and analytically engaged perspective.